A systematic review on sustainable practices transforming global agribusiness - Doda, Harshit; Sharma, Anshumant; Thakur, Neha (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe transformation of global agribusiness through sustainable practices has become a pressing priority to address environmental, economic, and social challenges.MethodsThis systematic review analyzed peer-reviewed literature from leading databases, applying predefined inclusion and exclusion criteria to evaluate the adoption and impact of sustainable practices in agribusiness.ResultsKey findings indicate that techniques such as precision agriculture, regenerative farming, renewable energy integration, and circular economy models significantly reduce resource consumption, enhance productivity, and promote socio-economic equity. Barriers include financial constraints, policy gaps, and limited technological access.Discussion and conclusionThe review provides actionable recommendations for stakeholders, emphasizing the importance of innovative solutions, supportive policy frameworks, and collaborative efforts to advance sustainable agribusiness globally.